Molecular evidence for polyphyletic origin of the primary symbionts of sucking lice (phthiraptera, anoplura) - Hypsa, Václav; Krízek, Jaroslav (Microbial ecology, 2007)
Based on 16S rDNA analyses, the primary symbionts of sucking lice were found to form a polyphyletic assemblage of several distant lineages that have arisen several times within Enterobacteriaceae and at least once within Legionellaceae. Another independent lineage of endosymbiotic enterobacteria inhabits a sister group of the sucking lice, Rhynchophthirina. The inspection of 16S rDNA supports the symbiotic nature of the investigated bacteria; they display a typical trait of degenerative processes, an increased AT content (Adenine-Thymine content) in comparison with free-living bacteria. The calculation of divergence time between the closest anopluran and rhynchophthirine symbionts further support their independent origin. The results shown here, together with evidence from other groups, indicate that the significance of primary symbionts for blood-feeding insects should be reconsidered.
Keywords: Animals; RNA, Ribosomal, 16S; Base Sequence; DNA, Mitochondrial; Bacterial Physiological Phenomena; ribozomální DNA; symbióza; zvířata; DNA, Ribosomal; Symbiosis; Bacteria; fyziologie bakterií; RNA ribozomální 16S; mitochondriální DNA; Phthiraptera; sekvence nukleotidů